2016
DOI: 10.2174/1389450116666150420143932
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Bone Microenvironment in Metastatic Castration-Resistant Prostate Cancer

Abstract: Metastatic castration-resistant prostate cancer (mCRPC) is universally incurable and represents an area of substantial unmet medical need. Novel targets and therapeutic strategies have emerged based on an improved understanding of the crosstalk between prostate cancer cells and the bone microenvironment. A wide variety of signaling systems including the RANKL/RANK/OPG, IGF-I, FGF and Wnt:DKK-1 pathways can be targeted to suppress tumor growth and treatment resistance. Antisurvival factor therapy can increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In contrast, biological mechanisms of resistance to conventional cytotoxic chemotherapeutics and targeted therapies designed for specific molecules share multiple features, including activated prosurvival pathways and disabled apoptotic machineries, together constituting response variation that awaits precise treatments [103]. For instance, metastatic castrationresistant prostate cancer (mCRPC) is usually incurable and represents an area of substantial unmet medical need, and multiple systems such as the RANKL/RANK/OPG, IGF-I, FGF and Wnt/DKK-1 pathways are targetable for suppression of tumor growth and therapeutic resistance [104]. Pathological roles of the TME in modulating tumor sensitivity are being increasingly recognized as a key aspect for development of modern anticancer therapeutics.…”
Section: Concluding Remarks and Future Avenuesmentioning
confidence: 99%
“…In contrast, biological mechanisms of resistance to conventional cytotoxic chemotherapeutics and targeted therapies designed for specific molecules share multiple features, including activated prosurvival pathways and disabled apoptotic machineries, together constituting response variation that awaits precise treatments [103]. For instance, metastatic castrationresistant prostate cancer (mCRPC) is usually incurable and represents an area of substantial unmet medical need, and multiple systems such as the RANKL/RANK/OPG, IGF-I, FGF and Wnt/DKK-1 pathways are targetable for suppression of tumor growth and therapeutic resistance [104]. Pathological roles of the TME in modulating tumor sensitivity are being increasingly recognized as a key aspect for development of modern anticancer therapeutics.…”
Section: Concluding Remarks and Future Avenuesmentioning
confidence: 99%
“… 216 The increased levels of parathyroid hormone-related peptide (PTHrP) from osteoclasts can induce bone resorption by upregulating the receptor activator of RANKL, which promotes the release of various growth factors (such as ionized calcium and TGFĪ²) into the bone microenvironment to support cancer cell implantation and transformation. 217 ā€“ 221 Invading tumor cells secrete osteolytic cytokines, such as granulocyte-macrophage colony-stimulating factor, matrix metalloproteinases, interleukin (IL)-6, insulin-like growth factors (IGFs), fibroblast growth factors (FGFs), endothelin 1, growth differentiation factor 15 (GDF15), dickkopf-1 (DKK-1), and WNTs. 222 ā€“ 226 These osteolytic cytokines stimulate preosteoblast differentiation and promote osteoclast maturation to accelerate bone resorption.…”
Section: Targeting Bone Microenvironmentmentioning
confidence: 99%
“…The insulin-like growth factor (IGF) signaling axis, composed of two receptors (IGF-IR and IGF-IIR) and their specific ligands (IGF-I and IGF-II), was widely shown to be up-regulated in PCa cells and tissues [ 185 , 186 , 187 ] and is now considered an effective molecular target for PCa therapy [ 188 , 189 , 190 ]. We reported that, in CRPC cells, GnRH agonists interfere with the protumoral activity of IGF-I, by reducing IGF-IR expression and activation (i.e., tyrosine phosphorylation) [ 21 , 159 ].…”
Section: The Gnrh/gnrh-r Axis In Crpcmentioning
confidence: 99%